2014
DOI: 10.1128/cvi.00786-13
|View full text |Cite
|
Sign up to set email alerts
|

Live Oral Salmonella enterica Serovar Typhi Vaccines Ty21a and CVD 909 Induce Opsonophagocytic Functional Antibodies in Humans That Cross-React withS. Paratyphi A andS. Paratyphi B

Abstract: S almonella enterica serovar Typhi (S. Typhi), a human-restricted pathogen, is the causative agent of typhoid fever, the most prevalent form of enteric fever, resulting in an estimated 21.7 million cases and 200,000 deaths per year worldwide (1). However, infection with Salmonella enterica serovar Paratyphi A (paratyphoid A fever) or Salmonella enterica serovar Paratyphi B (paratyphoid B fever) causes similar clinical manifestations (2). While less prevalent than typhoid fever, paratyphoid fever occurs in an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 52 publications
2
38
0
Order By: Relevance
“…Even in intracellular bacterial infections such as S. typhi , surface-binding antibodies are able to trigger killing by opsonophagocytosis during the extracellular phase of their lifecycles [55]. M.tb presents the substantial challenge of a lipid-rich cell membrane and less potential exposure to antibodies via haematogenous spread.…”
Section: Introductionmentioning
confidence: 99%
“…Even in intracellular bacterial infections such as S. typhi , surface-binding antibodies are able to trigger killing by opsonophagocytosis during the extracellular phase of their lifecycles [55]. M.tb presents the substantial challenge of a lipid-rich cell membrane and less potential exposure to antibodies via haematogenous spread.…”
Section: Introductionmentioning
confidence: 99%
“…A new generation of live oral typhoid vaccines has also been developed, of which two candidate strains remain in clinical development, M01ZH09 (Hindle et al, 2002;Kirkpatrick et al, 2005Kirkpatrick et al, , 2006Tran et al, 2010) and CVD 909 (Tacket et al, 2004b;Wahid et al, 2007Wahid et al, , 2011Wahid et al, , 2014Wang et al, 2000). The aim of these live oral vaccines is to equal Ty21a in safety but to surpass it in efficacy and to achieve this with the administration of a single dose.…”
Section: New Live Oral Typhoid Vaccinesmentioning
confidence: 97%
“…CVD 909 is unique among attenuated live oral S. Typhi vaccine candidates in having a mutation in the promoter of tviA, the first gene in the Vi biosynthesis locus; this results in the constitutive expression of Vi capsular polysaccharide. Both M01ZH09 and CVD 909 have been tested in phase 1 and 2 clinical trials and have been found to be well tolerated and immunogenic after ingestion of just a single oral dose (Kirkpatrick et al, 2005;Kirkpatrick et al, 2006;Tacket et al, 2004b;Tacket and Levine, 2007;Tran et al, 2010;Wahid et al, 2014). Oral single-dose immunization of adult volunteers with these vaccine strains elicits gut-derived IgA antibody-secreting cells and serum IgG and IgA antibodies to S. Typhi O antigen as well as S. Typhi-specific cell-mediated immune responses that are comparable to those obtained after immunization with four doses of Ty21a.…”
Section: New Live Oral Typhoid Vaccinesmentioning
confidence: 97%
See 1 more Smart Citation
“…As these vaccines enter clinical development, it is important to establish their immunogenicity through relevant, well-characterized immunological assays. There is a growing realization within the vaccinology community that in addition to determining antibody levels through binding assays, it is important to determine the functional, antimicrobial capacity of these antibodies.Although many studies have evaluated anti-Salmonella serum bactericidal and opsonophagocytic antibody activity (2,(8)(9)(10)(11)(12)(13)(14)(15), there is a need for reproducible assays that can be used routinely to characterize functional antibody responses to Salmonella in a standardized manner. We previously developed a complementdependent serum bactericidal antibody (SBA) activity assay that quantifies serum antibody responses to typhoidal (S. Typhi and S. Paratyphi A) and nontyphoidal (S. Typhimurium and S. Enteritidis) Salmonella (16).…”
mentioning
confidence: 99%